STRATEGY OF THE DEPARTMENT OF CULTURE AND TOURISM BOJONEGORO IN INCREASING CREATIVE INDUSTRY IN GEN-Z - Rizkiana, Afika; Wulandari, Septi; Lukita, Cahya; SEPTI WULANDARI (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the strategies used by the Bojonegoro Regency Culture and Tourism Office to increase the interest and participation of Generation Z in the creative industry. This research method uses qualitative descriptive research. Data collection techniques consist of primary data sources and secondary data. Primary data is obtained through interviews and observations, while secondary data is obtained through documentation studies. This study uses purposive sampling techniques to identify informants. Data validity techniques use source triangulation techniques. The results of this study indicate that the Bojonegoro Regency Culture and Tourism Office has empowered the younger generation through training programs, art festivals, and competitions. However, better policies and continued support are needed to address the key issues of Generation Z's interest in the creative industry. This study found that the Bojonegoro Regency Culture and Tourism Office can increase Generation Z's involvement in the creative industry by utilizing local cultural potential and providing access to technology. So, the Bojonegoro Regency Culture and Tourism Office can increase Generation Z's participation in the creative industry and help sustainable local economic growth by implementing a comprehensive strategy and gaining support from the government and local communities.